IMPROVING THE LEARNING OF ART MATERIALS THROUGH THE METHOD OF GIVING ASSIGNMENTS IN CLASS IV STUDENTS OF SDN WATUSAMPU - Hajna Hajna; Yun Ratna Lagandesa (Universitas Tadulako, 2020)
Main problem in this study is inferiority of learning result by SDN Watusampu’s 4th grade students on arts and talent. This study purpose is proofing how giving task methods can improve SDN Watusampu 4th grade student’s learning results of arts’ class. This study’s sample is 31 students. Type of this study is study of action class which have 2 cycles, each cycles composed of planning, implementation, observation, and reflection. Result of this study proving there’s improving of student’s learning result from first cycle to the second cycle. Study’s result on first cycle obtained result students who pass the class are 12 with percentage 38,71%, while on second cycle get significant improving with students who pass the class are 29 with percentage 93,55% and only 2 students yet. It shown from first cycle to the second cycle have improving 54,84%. According to this study, using giving task methods which implicated on art’s class can improving learning process on SDN Watusampu’s 4th grade students.